IL-7 Induces an Epitope Masking of γc Protein in IL-7 Receptor Signaling Complex - Goh, Tae Sik; Jo, Yuna; Lee, Byunghyuk; Kim, Geona; Hwang, Hyunju; Ko, Eunhee; Kang, Seung Wan; Oh, Sae-Ock; Baek, Sun-Yong; Yoon, Sik; Lee, Jung Sub; Hong, Changwan (Mediators of Inflammation, 2017)
IL-7 signaling via IL-7Rα and common γ-chain (γc) is necessary for the development and homeostasis of T cells. Although the delicate mechanism in which IL-7Rα downregulation allows the homeostasis of T cell with limited IL-7 has been well known, the exact mechanism behind the interaction between IL-7Rα and γc in the absence or presence of IL-7 remains unclear. Additionally, we are still uncertain as to how only IL-7Rα is separately downregulated by the binding of IL-7 from the IL-7Rα/γc complex. We demonstrate here that 4G3, TUGm2, and 3E12 epitope masking of γc protein are induced in the presence of IL-7, indicating that the epitope alteration is induced by IL-7 binding to the preassembled receptor core. Moreover, the epitope masking of γc protein is inversely correlated with the expression of IL-7Rα upon IL-7 binding, implying that the structural alteration of γc might be involved in the regulation of IL-7Rα expression. The conformational change in γc upon IL-7 binding may contribute not only to forming the functional IL-7 signaling complex but also to optimally regulating the expression of IL-7Rα.